Hemoperitoneum: a rare complication caused by a leiomyoma - Moreira,Marta Sales (2021)
Abstract Uterine leiomyomas are the most common gynecologic tumors and occur commonly in women of reproductive age1. Frequently they are asymptomatic, but they can present with abnormal uterine bleeding, abdominal pain and pressure symptoms if there is a large tumor size2. Hemoperitoneum due to spontaneous bleeding from a uterine leiomyoma is an extremely rare situation, with less than 100 cases described in literature3. We report a case of a 46 -year- old woman presenting acute abdominal pain with a spontaneous hemoperitoneum caused by a uterine leiomyoma.